C3 and C4 Complements in Glomerular Disorders in Children - H. Alatas; I.G.N. Wila Wirya; T. Tambunan (Indonesian Pediatric Society, 1978)
Seventy children who were hospitalized for kidney diseases in the Nephrological ward Department of Child Health, University of Indonesia, Jakarta were used in this study. Thirty seven patients sufferfng from acute poststreptococcal Glomerulonephritis (A.G.N.), 3 patients with Membranoproliferative Glomerulonephritis (M.P.G.N.) and 30 patients with Nephrotic Syndrome due to other causes were examined for complement concentration. A total of 80 samples were examined for C3 and 25 samples for C4 concentration using the immunediffusion plates. Almost all patients with A.G.N. and M.P.G.N. showed depression of C3. C4 concentration was normal except in 2 patients, 1 with A.G.N. and the other With M.P.G.N. This suggest activation of complement at the C3 level by the alternating pathway in most of the patients. C3 concentration in A.G.N. patients returned to normal after 8-10 weeks. In MPGN the depression was persistent in 2 patients, while in 1 patient it returned to normal level after 3 months of Immunosuppressive treatment.